Establishment of Intl. standard tourism complex at existing Motel Upal compound of BPC at Cox’s Bazar - Mahbub, Zareen Tasnim (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2019.